Surgical management of early stage invasive breast cancer: a practice guideline - McCready, David (Canadian Medical Association, 2005)
OBJECTIVES: To assess the available evidence on sentinel lymph-node biopsy, and to examine the long-term follow-up data from large randomized phase III trials comparing breast-conserving therapy with mastectomy in order to make recommendations on the surgical management of early invasive breast cancer (stages I and II), including the optimum management of the axillary nodes: for the breast — modified radical mastectomy or breast-conserving therapy; for the axilla — complete axillary node dissection, axillary dissection of levels I and II lymph nodes, sentinel lymph-node biopsy or no axillary node surgery. OUTCOMES: Overall survival, disease-free survival, local recurrence, distant recurrence and quality of life. EVIDENCE: MEDLINE, EMBASE, the Cochrane Library databases and relevant conference proceedings were searched to identify randomized trials and meta-analyses. Two members of the Practice Guidelines Initiative, Breast Cancer Disease Site Group (BCDSG) selected and reviewed studies that met the inclusion criteria. The systematic literature review was combined with a consensus process for interpretation of the evidence to develop evidence-based recommendations. This practice guideline has been reviewed and approved by the BCDSG, comprising surgeons, medical oncologists, radiation oncologists, pathologists, a medical sociologist, a nurse representative and a community representative. BENEFITS, HARMS AND COSTS: Breast-conserving therapy (lumpectomy with levels I and II axillary node dissection, plus radiotherapy) provides comparable overall and disease-free survival to modified radical mastectomy. Levels I and II axillary dissection accurately stages the axilla and minimizes the morbidity of axillary recurrence but is associated with lymphedema in approximately 20% of patients and arm pain in approximately 33%. Currently, there is insufficient data regarding locoregional recurrence and long-term morbidity associated with sentinel-node biopsy to advocate it as the standard of care. Breast-conserving therapy may offer an advantage over mastectomy in terms of body image, psychological and social adjustment but appears equivalent with regard to marital adjustment, global adjustment and fear of recurrence. RECOMMENDATIONS: Women who are eligible for breast-conserving surgery should be offered the choice of either breast-conserving therapy with axillary dissection or modified radical mastectomy. Removal and pathological examination of levels I and II axillary lymph nodes should be the standard practice in most cases of stages I and II breast carcinoma. There is promising but limited evidence to support recommendations regarding sentinel lymph-node biopsy alone. Patients should be encouraged to participate in clinical trials investigating this procedure. VALIDATION: A draft version of this practice guideline and a 21-item feedback questionnaire was circulated to 201 practitioners in Ontario. Of the 131 practitioners who returned the questionnaire, 98 (75%) completed the survey and indicated that the report was relevant to their clinical practice. Eighty (82%) of these practitioners agreed that the draft document should be approved as a practice guideline. SPONSORS: The Practice Guidelines Initiative is supported by Cancer Care Ontario and the Ontario Ministry of Health and Long-Term Care. COMPLETION DATE: Jan. 21, 2003.